Valores do dinheiro, percepção e comportamento de risco entre universitários - Santos, Anavaleria Vieira (2014)
This study investigates the relationship between the values of money, perception and risk behavior among college Maranhão. The study is characterized as a descriptive and quantitative research, being studied in the population of young undergraduates enrolled in courses at the Center for Social Sciences at the Federal University of Maranhão sample, and the survey instrument consists of questions based on the Meaning Scale money (Moreira; Tamayo, 1999) and Perception Scale and Intent to present behavior of Risk (WEBER; BLAIS; BETZ, 2002; PAULINE, 2009). Data were collected at random in the city of Sao Luis MA, in a survey of 363 college students. As the main technical Correspondence Analysis, whose results were obtained from the perception of study participants, represented visually in the form of geographical maps was used, detecting the close relations between the constructs values of money, loss aversion, perception risk and risk behavior. The main results show that subjects who had medium and high levels of cash values to have a close relationship with and who had high average rating for loss aversion. It is noticed also that there is a close relationship between respondents who had high and average perception of money values with high and medium risk perception, and the existence of a close relationship between those who obtained high and medium value of money with medium risk and low, these results indicate that among the university higher levels of cash values o be linked with lower levels of risk (perception + behavior). The main results indicate that the investigated sample perceived high values for the money, the positive and negative dimensions, indicate an average risk perception and behavior of conservative risk.